Photochemical Synthesis of Fused Indole Derivatives - Samsonenko, Anna L.; Kostyuchenko, Anastasia S.; Zheleznova, Tatyana Yu.; Uliankin, Evgenii B.; Shuvalov, Vladislav Yu.; Shatsauskas, Anton L.; Chernenko, Sergei А.; Fisyuk, Alexander S. (Synthesis, 2025)
A new approach is proposed for the synthesis of fused indole derivatives based on 4,5-diaryl-substituted 1H-pyrrole-2-carboxylates. Iodine-promoted photochemical cyclization of 4,5-diaryl-substituted 1H-pyrrole-2-carboxylates leading to 1H-dithieno[2,3-e:3′,2′-g]indoles, 10H-benzo[e]thieno[3,2-g]indoles, 1H-dibenzo[e,g]indoles, and 3,6-dihydrobenzo[4,5]indolo[7,6-c]carbazoles was studied.
Keywords: cyclization; fused-ring systems; heterocycles; indole derivatives; photochemistry